Universalising the concept of identity with islamic theological perspective (2016)
This paper discussed the universality of the concept of identity from the perception of Islam. This perspective of Islam was deemed necessary as a gap to be filled at ensuring that identity completes its course of universality as a concept. Therefore, the study subjected identity in its types to a Quranic critique with a view to identifying those that are in tandem with the tenets of Islam and those that are at variance with them. The contributions of Islam were critically discussed from four major schools of identity around the Muslim world. These schools with different formational motives and objectives were identified as the traditionalist, the reactionary, the non-conformist and the modernist. The paper argued that the four schools of identity, inspit of their differences, were formed with the aim of achieving the same goal of the preservation of the sanctity of Islam but using different theological mechanisms. With the perspectives of Islam, identity as a concept was adjudged to have completed as cycle of universality. Conclusively, it was advanced that the primary basis in the formation of the four schools identity is the Quran. As such, the basis should be used as the yardstick for rejecting any of the views expressed by those schools or their likes which may come on board to further contribute to the concept of identity from Islamic viewpoints.